KAJIAN ILMIAH PENYEBAB HAMPIR PUNAHNYA POPULASI IKAN BILIH DI PERAIRAN DANAU TOBA - Pohan Panjaitan ,; Rumondang Rumondang ,; Juliwati Putri Batubara (Universitas Asahan, 2022)
ABSTRACT Bilih fishes (Mystacoleucus padangensis Bleeker) is not native species of Lake Toba, other wise it is from Lake Singkarak, West Sumatra. There is a sharp increase in the population number of bilih fishes in Lake Toba due to water quality of Lake Toba supports the life of bilih fishes. Therefore fishermen of Lake Toba get benefit from the high growth of bilih fishes. However nowdays the population of bilih fish in the waters of Lake Toba is almost extinct due to several reasons, including: (a) the conservation area of bilih fish has not been established and (b) there are no regulations limiting fishing locations and fishing gear used for bilih fish species. There are a number of strategies that have been implemented to implement efforts to preserve the bilih fish population in the waters of Lake Toba, including: (1) determination of the fishing area and conservation area for the Bilid fish; (2) population in the Lake Toba waters along with the waters that regulate it determination of the size of fish and the size of the nets that are allowed to catch bilih fish and the number of bilih fish that are allowed to be caught every day from the waters of Dabau Toba; (3) education of the fishing community about the ecobiology of bilih fish; and (4) biophysical improvement of the Lake Toba area Key wold: native species, population, bio-ecology, sustainable fisheries